Partisipasi Masyarakat Terhadap Program Keluarga Berencana (Studi Fenomenologi Terhadap Masyarakat Di Dusun Karanggawang, Desa Pagersari, Kecamatan Mungkid, Kabupaten Magelang) - Alfan Biroli (DIMENSI - Jurnal Sosiologi, 2015)
Karanggawang society have been autonomy in strategy of make little family who well being and happiness with KB program. Thus, this research have purpose to know how society can participate to planning family program. This program aim to wipes and husband. The theory is used as analysis is masculinity dominant by Pierre Bourdieu theory. This research is done in Karanggawang and Pagersari village, Mungkid, Magelang residence. Variety of research is qualitative with strategy phenomenology. The result of research have been shown that society program to KB there were unsuitable position between women and men in to take decision. KB program participation more dominant women than men. In the society have been constructed that KB program only to women not men. Whereas, the basically KB program can be join by women or men. Conservative social structure still use dominant patriarchy system. So that, men have big power than women, so women just receive and become subordinate in the family and social environment.